High-conductivity composition as well as preparation method, cosmetic and application thereof

By using a specific proportion of hydrolyzed soy protein, emollient, oil-phase thickener and aqueous components in cosmetics, the problem of difficulty in maintaining safety and stability in cosmetics when improving conductivity is solved, and cosmetics with high conductivity and good stability are achieved, and suitable for use with radio frequency or micro current beauty instruments.

CN119548426APending Publication Date: 2025-03-04FLOSSOM (GD) BEAUTY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411797796.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing cosmetics are difficult to maintain product safety and stability while improving conductivity, especially when used with radio frequency or micro current beauty instruments.

Method used

A high conductivity composition is used, which includes a specific proportion of hydrolyzed soy protein, emollient, oil-phase thickening agent and aqueous components. Through the combination and proportion of these components, high conductivity is achieved without the need for the addition of electrolytes or emulsifiers.

Benefits of technology

Cosmetics with high conductivity have good stability and safety, which can improve the body feeling and effect of the beauty instrument, while ensuring the safety and stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119548426A_ABST
    Figure CN119548426A_ABST
Patent Text Reader

Abstract

The invention provides a high-conductivity composition as well as a preparation method, cosmetics and application thereof, and belongs to the technical field of cosmetics. The high-conductivity composition according to the present invention comprises 0.5-1.5% by mass of hydrolyzed soy protein, 10-40% by mass of an emollient, 0.5-7% by mass of an oil-phase thickener, and the balance of an aqueous component with respect to 100% by mass of the high-conductivity composition. According to the high-conductivity composition disclosed by the invention, through specific components and proportions, the high-conductivity composition has relatively high conductivity under the condition that no electrolyte is added and no emulsifier is contained, and the conductivity range is 600-2000 [mu] S / cm; and the composition has stability. The preparation method of the high-conductivity composition is simple and suitable for large-scale production and application. The cosmetic containing the high-conductivity composition can further improve the efficacy by promoting the permeation of the active components compared with conventional cosmetics when the active components are used together with a radio frequency cosmetic instrument or a micro-current cosmetic instrument.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cosmetics, and in particular to a high-conductivity composition and a preparation method thereof, cosmetics and applications. Background Art

[0002] The electrical impedance characteristics of the stratum corneum of the skin are closely related to electrical conductivity. Electrical impedance is a physical quantity that represents the degree of resistance encountered when electric current passes through a substance, while electrical conductivity is a measure of the material's ability to conduct electricity. In the application of beauty devices, especially radio frequency and microcurrent technology, the electrical impedance characteristics of the skin directly affect the efficiency of energy transfer in the skin. When energy such as radio frequency or microcurrent acts on the skin, the skin tissue will generate impedance, thereby hindering the transfer of energy. The size of the impedance depends on factors such as the electrical conductivity of the skin tissue.

[0003] Radio frequency beauty technology uses radio frequency energy to penetrate the skin, and acts on the deep skin tissue by heating, prompting collagen to contract and regenerate, so as to achieve the effect of firming the skin and reducing wrinkles. In this process, the transmission efficiency of radio frequency energy is affected by the impedance of skin tissue. Too high impedance will reduce the effective transmission of energy and reduce the effect of radio frequency beauty. Therefore, reducing the electrical impedance of the stratum corneum of the skin and increasing its conductivity will help radio frequency energy to be more effectively transmitted to the deep layer of the skin, thereby improving the beauty effect. Microcurrent beauty devices stimulate the skin by applying weak currents, promoting muscle contraction and lymphatic circulation, so as to achieve the effects of firming and removing edema. Similarly, the transmission efficiency of current is also affected by the electrical impedance of the skin. High conductivity can better conduct current, making the effect of microcurrent beauty devices more significant.

[0004] Existing studies have shown that the impedance of the stratum corneum of the skin can be changed by using skin care cosmetics. Due to the formula structure, it is difficult for conventional skin care cosmetics to meet the effect of changing the impedance of the stratum corneum of the skin through higher conductivity. Unlike conventional skin care cosmetics, cosmetics used with beauty devices such as radio frequency and microcurrent need to have higher conductivity, which can not only improve the physical sensation of product use (such as current sense, warm feeling, etc.), but also increase energy input, thereby achieving better results. Methods for improving the conductivity of cosmetics mainly include the use of anionic emulsifiers and added electrolytes, however, these methods also have some disadvantages: for example, anionic emulsifiers may disturb the intercellular lipids of the stratum corneum and cause skin irritation problems; and added electrolytes may make it difficult to thicken the formula and reduce the stability of the emulsion. In addition, CN1917850B mentions the use of lysophospholipids as emulsifiers and the method of controlling the particle size of the emulsion droplets at 30 to 300 nm, which can achieve the stability of the beauty solution with high electrolyte content, but this requires the use of a high-pressure homogenizer, and the process is relatively complicated. Although this method can improve the conductivity of cosmetics, the complexity of the production process may affect its application in commercial products.

[0005] In summary, the relationship between the electrical impedance characteristics and conductivity of the skin stratum corneum is crucial to the energy transfer efficiency of beauty devices, and the method of improving the conductivity of cosmetics needs to find a balance between improving the effect and ensuring product safety and stability. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention discloses a high conductivity composition and a preparation method thereof, cosmetics and applications, aiming to solve the problem of improving the conductivity of cosmetics while maintaining their safety and stability.

[0007] In one aspect, the present invention provides a high conductivity composition, comprising 0.5-1.5 mass % of hydrolyzed soy protein, 10-40 mass % of emollient, 0.5-7 mass % of oil phase thickener and the balance of aqueous components relative to 100 mass % of the high conductivity composition.

[0008] The high conductivity composition proposed by the present invention has high conductivity without adding electrolytes of organic or inorganic compounds that can spontaneously ionize in water to generate a large amount of anions and cations, and without using any anionic, cationic or non-ionic emulsifiers, through specific components and proportions. The conductivity range of the present invention is 600-2000 μS / cm, and its safety is guaranteed while having high conductivity, and the composition has stability.

[0009] In the high conductivity composition of the present invention, each component has high conductivity and stability only in a specific proportion: the component that affects the conductivity in the composition is mainly hydrolyzed soy protein. Since the protein molecule contains acidic amino acids, the carboxyl groups of these amino acids can release negative charges in aqueous solution, so the hydrolyzed soy protein itself carries negative charges. At the same time, the droplets formed by the hydrolyzed soy protein are very small, and the surface to volume ratio is very large, so that these negative charges are adsorbed and concentrated on the surface of the droplets, further increasing the conductivity of the droplets. However, the research and development team of the present invention found that the hydrolyzed soy protein in the composition has high conductivity and stability only in the range of 0.5% to 1.5%. If the amount of hydrolyzed soy protein is less than 0.5%, the conductivity will decrease, and the stability will decrease; when the amount is higher than 1.5%, a darker color will be produced, affecting the appearance. At the same time, by adding a specific proportion of emollients, oil phase thickeners, and aqueous components and hydrolyzed soy protein to the composition, the function of stabilizing the water-oil two phases is achieved, forming a similar emulsification system, achieving an emulsification effect, and making the composition stable. The content of the emollient in the present invention is 10% to 40%, and different moisturizing sensations can be achieved by adjusting the amount of the emollient. When the amount of the emollient is higher than 40%, the emulsification stability deteriorates, but when the amount of the emollient is lower than 10%, it will result in insufficient oiliness and affect the feeling of use. The content of the oil phase thickener is 0.5% to 7%, and this ingredient is used to adjust the viscosity and texture of the product. When the amount of the oil phase thickener is lower than 0.5%, it will result in low viscosity and poor stability, and when the amount is higher than 7%, there will be a problem of crystallization. The remaining amount of the aqueous component is to maintain the fluidity and easy application of the composition.

[0010] Through the above specific composition formula design, the composition can provide high conductivity and good stability without using emulsifiers that may cause skin irritation or added electrolytes that may cause formula stability problems, which is an important advantage for products used with beauty devices. Such a composition can not only improve the physical feel and effect of the beauty device, but also ensure the safety and stability of the product, meeting consumers' demand for high-quality cosmetics.

[0011] Furthermore, the high conductivity composition of the present invention comprises 0.7% to 1.5% by mass of hydrolyzed soy protein, 10% to 30% by mass of emollient, 0.5% to 5% by mass of oil phase thickener and the balance of aqueous components relative to 100% by mass of the high conductivity composition. The embodiments of the present invention show the relevant components and their contents.

[0012] Furthermore, the mass ratio of the hydrolyzed soy protein to the emollient is 1:(15-25), preferably 1:(15-20). The research and development team of the present invention unexpectedly discovered through experiments on instant emulsification effect and high and low temperature stability that the hydrolyzed soy protein and emollient of the present invention are only stable at a mass ratio of 1:(15-25). If the mass ratio of the hydrolyzed soy protein to the emollient exceeds the range of 1:(15-25), unstable phenomena such as yellowing and demulsification will occur.

[0013] Furthermore, the molecular weight of the hydrolyzed soybean is 10,000 to 30,000 Daltons, preferably 20,000 Daltons. Optionally, the hydrolyzed soybean protein with a molecular weight of 1 to 3 Daltons of the present invention can be purchased from commercial products. When the molecular weight of the hydrolyzed soybean is 10,000 to 30,000 Daltons, the hydrolyzed soybean is hydrolyzed with soybean protease to produce a hydrophilic and lipophilic amphiphilic polypeptide component, and the amphiphilic polypeptide component stabilizes the composition. The embodiments of the present invention show the effects of different hydrolyzed soybean proteins on the composition.

[0014] The research and development team of the present invention found through instant emulsification effect and high and low temperature stability experimental tests that not all thickeners are suitable for the high conductivity composition of the present invention; preferably, the oil phase thickener is at least one of pentaerythritol tetrastearate, dextrin palmitate, synthetic wax, synthetic spermaceti, cetyl palmitate, cetyl alcohol, stearyl alcohol, cetyl stearyl alcohol, and stearic acid, preferably at least one of cetyl stearyl alcohol and cetyl palmitate.

[0015] Further, the emollient is at least one of jojoba (SIMMONDSIA CHINENSIS) seed oil, white pond flower (LIMNANTHES ALBA) seed oil, avocado tree (BUTYROSPERMUM PARKII) fruit fat, inca inchi (PLUKENETIAVOLUBILIS) seed oil, oat (AVENA SATIVA) kernel oil, safflower (CARTHAMUS TINCTORIUS) seed oil, squalane, hydrogenated polyisobutene, hydrogenated polydecene, caprylic / capric triglyceride, polydimethylsiloxane, coconut oil alcohol-caprylate / caprate, pentaerythritol tetra(ethylhexanoate), and propylene carbonate, preferably at least one of hydrogenated polyisobutene, polydimethylsiloxane, and caprylic / capric triglyceride.

[0016] On the other hand, the present invention also provides a method for preparing a high conductivity composition, wherein an emollient and an oil phase thickener are heated to 80-85°C to obtain an oil phase component; hydrolyzed soy protein and an aqueous component are evenly mixed and heated to 80-85°C to obtain an aqueous phase component; the oil phase component is added to the aqueous phase component and then homogenized and emulsified to obtain a high conductivity composition. The method for preparing the high conductivity composition of the present invention is simple and suitable for large-scale production applications.

[0017] On the other hand, the present invention also provides a cosmetic of a high conductivity composition, which, relative to 100% by mass of the cosmetic, consists of 10 to 40% by mass of an emollient, 0.5% to 1.5% by mass of hydrolyzed soy protein, 0.5 to 7% by mass of an oil phase thickener, 1 to 10% by mass of a polyol, 0.1 to 1% by mass of an aqueous thickener, 1 to 5% by mass of an active ingredient, 0.5 to 1.5% by mass of a preservative and the remainder water.

[0018] Optionally, the polyol is at least one of glycerol, propylene glycol, 1,3-propanediol, butylene glycol, dipropylene glycol, diglycerol, PEG-400, PE-75, PEG / PPG-14 / 7 dimethyl ether, methyl propanediol, 1,2-pentanediol, and PEG / PPG / polybutylene glycol-8 / 5 / 3 glycerol.

[0019] Optionally, the aqueous thickener is at least one of xanthan gum, sclerotium gum, taro gum, tamarind seed polysaccharide, hydroxyethyl cellulose, cellulose gum, and polyacrylate cross-linked polymer-6. Too little aqueous thickener will result in too low viscosity and reduced stability, while too much aqueous thickener will result in a sticky skin feel and a mud-like problem.

[0020] Optionally, the active ingredients include hyaluronic acid, sodium gamma-polyglutamate, carnosine, collagen, soluble collagen, collagen amino acids, ergothioneine, tetrahydromethylpyrimidine carboxylic acid, acetyl hexapeptide-8, palmitoyl tripeptide-5, hydroxypropyl tetrahydropyrantriol, hydroxypinacolone retinoic acid ester, niacinamide, glabridin, phenethyl resorcinol, hexyl resorcinol, bifid yeast fermentation product lysate, bisabolol, ginger root extract, African cardamom seed extract, glycerophosphoinositol choline salt, cherimoya extract, hydrolyzed algae extract, kava pepper extract, citrus peel extract, spring onion extract. In a high conductivity system, the active ingredients can synergistically enhance the transdermal absorption effect under the action of electric current, thereby exerting better efficacy.

[0021] Optionally, the preservative includes at least one of phenoxyethanol, caprylyl glycol, p-hydroxyacetophenone, raspberry ketone, ethylhexylglycerin, sodium benzoate, and potassium sorbate.

[0022] Furthermore, the cosmetic is any one of lotion, essence or emulsion.

[0023] Optionally, the cosmetics can be used daily or in conjunction with a beauty instrument.

[0024] On the other hand, the present invention also provides a combination of a high conductivity composition and a beauty instrument, wherein the beauty instrument is any one of a radio frequency beauty instrument and a microcurrent beauty instrument. The high conductivity composition of the present invention can be used in conjunction with a radio frequency beauty instrument or a microcurrent beauty instrument, and has a stronger current sensation and better immediate effect.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The high conductivity composition of the present invention has a high conductivity in the range of 600-2000 μS / cm without adding electrolytes and emulsifiers through specific components and proportions; and the composition is stable.

[0027] (2) The preparation method of the high conductivity composition of the present invention is simple and suitable for large-scale production applications.

[0028] (3) The high conductivity composition of the cosmetics of the present invention can further enhance the efficacy of the active ingredients by promoting the penetration of the active ingredients when used in conjunction with beauty equipment, compared with conventional cosmetics.

[0029] (4) The high conductivity composition of the present invention can be used in conjunction with a radio frequency beauty device or a microcurrent beauty device, and has a stronger current sensation and better immediate effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0031] Figure 1 The material surface appearance diagram showing the instant emulsification effect of Formula Comparative Example 1, Formula Example 3 and Formula Comparative Example 5;

[0032] Figure 2 The surface appearance of the material body of Formula Comparative Example 1, Formula Example 3 and Formula Comparative Example 5 after one month of high temperature stability test is shown;

[0033] Figure 3 The surface appearance of the material body of Formula Comparative Example 1, Formula Example 3 and Formula Comparative Example 5 after one month of low stability testing is shown;

[0034] Figure 4 Polarized light microscope test images of Formula Comparative Example 2 and Formula Example 1 are shown, wherein (a) is a polarized light microscope test image of Formula Comparative Example 2, and (b) is a polarized light microscope test image of Formula Example 1;

[0035] Figure 5A comparison chart showing the penetration effect of acetyl hexapeptide-8 under the action of a beauty instrument;

[0036] Figure 6 The thermal imaging images of Formula Comparative Example 2 and Formula Example 1 are shown, wherein (a) is the thermal imaging image of Formula Comparative Example 2, and (b) is the thermal imaging image of Formula Example 1. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] "Comprising" or "including" is intended to indicate that compositions and methods include the listed elements, but do not exclude other elements. "Consisting of" means excluding trace elements of other components and substantial method steps. Embodiments defined by each of these transition terms are within the scope of this application.

[0039] The raw materials and equipment used in this application, unless otherwise specified, are all commonly used raw materials and equipment in this field, and are all commercially available products. The methods used in this application, unless otherwise specified, are all conventional methods in this field.

[0040] Conductivity

[0041] The conductivity described in the embodiment is obtained by testing with a conductivity meter, and the model of the conductivity meter is: DDS-307A. Conductivity is a measurement value that indicates the strength of a substance's ability to transmit current. In the field of cosmetics, conductivity is generally controlled at a low level, mainly because higher conductivity will affect the stability of the formula and cause problems and challenges with thickening. As cosmetics used in conjunction with some beauty instruments, they must have a higher and appropriate conductivity level. This is mainly because some beauty instruments act on the skin through the principle of electrothermal heating, and conductivity plays an important role in exerting effects and user experience. The high conductivity described in the present invention is between 600-2000μS / cm.

[0042] Emollients

[0043] The emollient of the present invention is at least one of jojoba (SIMMONDSIA CHINENSIS) seed oil, white pond flower (LIMNANTHESALBA) seed oil, butyrospermum parkii (BUTYROSPERMUM PARKII) fruit fat, inca inchi (PLUKENETIA VOLUBILIS) seed oil, oat (AVENA SATIVA) kernel oil, safflower (CARTHAMUS TINCTORIUS) seed oil, squalane, hydrogenated polyisobutene, hydrogenated polydecene, caprylic acid / capric acid triglyceride, polydimethylsiloxane, coconut oil alcohol-caprylate / caprate, pentaerythritol tetra (ethylhexanoate), and propylene carbonate. In a preferred embodiment, the emollient is selected from at least one of hydrogenated polyisobutene, polydimethylsiloxane, caprylic acid / capric acid triglyceride. The emollients of three types of different structures and different polarities, hydrocarbons, silicone oils, and esters, represent the categories of commonly used emollients. It is further preferred that three emollients are used in combination.

[0044] Oil phase thickener

[0045] Oil phase thickener refers to a raw material used to increase or change the viscosity of the oil phase of cosmetics. Its thickening mechanism refers to the ability to achieve a thickening effect in the oil phase through swelling. The ester or solid oil composed of high-carbon fatty acids and high-carbon fatty alcohols has strong viscosity and adhesion, and can form a network structure in the oil phase liquid, thereby increasing the viscosity and consistency of the oil phase. The oil phase thickener is selected from at least one of pentaerythritol tetrastearate, dextrin palmitate, synthetic wax, synthetic spermaceti, cetyl palmitate, cetyl alcohol, stearyl alcohol, cetyl stearyl alcohol, and stearic acid. In a preferred embodiment, the oil phase thickener is selected from at least one of cetyl stearyl alcohol and cetyl palmitate.

[0046] Hydrolyzed soy protein

[0047] The technical solution of the present invention does not use an emulsifier, but achieves the function of stabilizing the water-oil phase through natural hydrolyzed soy protein. Hydrolyzed soy protein is hydrolyzed by soybean protease to produce a hydrophilic and lipophilic amphiphilic polypeptide component with a molecular weight of 10,000 to 30,000 Daltons. The hydrolyzed soy protein described in the preferred embodiment is purchased from Yulishidai (Beijing) Biotechnology Co., Ltd., trade name MIRA-MAP 2.0, with a molecular weight of about 20,000.

[0048] The hydrolyzed soy protein in Formula Comparative Example 1 was randomly selected from commercially available products and purchased from Ashland under the trade name Dynachondrine ISR, which is a non-amphiphilic polypeptide component obtained by hydrolyzing soy protein.

[0049] Emulsified cosmetics use emulsifiers as stabilizers to reduce the surface tension of the water and oil phases. Common cosmetic emulsifiers include anionic emulsifiers, nonionic emulsifiers, and cationic emulsifiers. In Formula Comparative Example 2, glyceryl stearate / PEG-100 stearate, an emulsifier commonly used in cosmetics, is used for effect comparison.

[0050] Polyols

[0051] The polyol is selected from at least one of glycerol, propylene glycol, 1,3-propanediol, butylene glycol, dipropylene glycol, diglycerol, PEG-400, PE-75, PEG / PPG-14 / 7 dimethyl ether, methyl propanediol, 1,2-pentanediol, and PEG / PPG / polybutylene glycol-8 / 5 / 3 glycerol. In a preferred embodiment, the polyol is selected from glycerol and butylene glycol.

[0052] Water-based thickener

[0053] The aqueous thickener is selected from at least one of xanthan gum, sclerotium gum, taro gum, tamarind seed polysaccharide, hydroxyethyl cellulose, cellulose gum, and polyacrylate cross-linked polymer-6. Carbomer aqueous thickeners and acrylic thickeners that need to be neutralized are not contained because additional electrolytes will be introduced during neutralization. It is further preferred that xanthan gum and polyacrylate cross-linked polymer-6 are compounded as the aqueous thickener.

[0054] preservative

[0055] The preservative is selected from at least one of phenoxyethanol, caprylyl glycol, p-hydroxyacetophenone, raspberry ketone, ethylhexylglycerin, sodium benzoate, and potassium sorbate. In a preferred embodiment, the preservative is selected from phenoxyethanol and ethylhexylglycerin.

[0056] Active ingredients

[0057] The active ingredients include one or more of hyaluronic acid, sodium γ-polyglutamate, carnosine, collagen, soluble collagen, collagen amino acids, ergothioneine, tetrahydromethylpyrimidine carboxylic acid, acetyl hexapeptide-8, palmitoyl tripeptide-5, hydroxypropyl tetrahydropyrantriol, hydroxypinacolone retinoic acid ester, niacinamide, glycyrrhizin, phenethyl resorcinol, hexyl resorcinol, bifid yeast fermentation product lysate, bisabolol, ginger root extract, African cardamom seed extract, glycerophosphoinositol choline salt, cherimoya extract, hydrolyzed algae extract, kava extract, citrus peel extract, and spring onion extract.

[0058] In a preferred embodiment, the active ingredient is selected from at least one of acetyl hexapeptide-8, palmitoyl tripeptide-5, carnosine, and niacinamide.

[0059] (1) Acetyl Hexapeptide-8

[0060] Also known as Argireline, it is a polypeptide composed of six amino acids that mimics the N-terminus of the SNAP-25 protein. It can reduce the force of muscle contraction, relax muscles, reduce the occurrence of dynamic lines and eliminate fine lines.

[0061] (2) Palmitoyl Tripeptide-5

[0062] Palmitoyl tripeptide-5 is a synthetic signal peptide that can mimic the function of TSP-1 and promote TGF-β, thereby increasing the production of collagen and reducing wrinkles. Palmitoyl tripeptide-5 can also inhibit the activity of matrix metalloproteinases MMP-1 and MMP-3 and the production of inflammatory factors interleukin 8 and TNF-α, preventing collagen from being decomposed.

[0063] (3) Carnosine

[0064] Carnosine is a dipeptide composed of two amino acids, β-alanine and L-histidine, which can promote the synthesis of collagen and elastic fibers, improve the elasticity and firmness of the skin, and reduce fine lines and wrinkles. Carnosine can inhibit the glycation reaction of proteins. At the same time, carnosine can interact with glycated protein products to prevent further cross-linking of glycated proteins.

[0065] (4) Niacinamide

[0066] Niacinamide can inhibit the process of melanocytes transferring melanosomes to keratinocytes, promote the renewal of the stratum corneum, and accelerate the metabolism of the formed melanin, thereby achieving the effect of whitening and brightening.

[0067] The high conductivity composition and its preparation method, cosmetics and applications of the present invention are further described below through specific examples and experimental tests.

[0068] Example 1 Formulation Preparation Example

[0069] According to the composition and content of each component in Table 1, the formula examples and formula comparative examples are prepared. In phase A, hydrogenated polyisobutene, polydimethylsiloxane, caprylic / capric triglyceride are emollients; glyceryl stearate and PEG-100 stearate are commonly used emulsifiers in cosmetics; cetearyl alcohol and cetyl palmitate are oil phase thickeners; hydrogenated palm kernel oil and hydrogenated coconut oil glycerides are oil phase thickeners that are not within the scope of the present invention. In phase B, glycerol and butylene glycol are polyols; polyacrylate cross-linked polymer-6 and xanthan gum are aqueous thickeners. In phase C, acetyl hexapeptide-8 and carnosine are functional active ingredients; phenoxyethanol and ethylhexylglycerin are preservatives.

[0070] Table 1 Recipe preparation table

[0071]

[0072] The preparation method of the above formulation preparation example is as follows:

[0073] Step 1: Mix the ingredients of phase A and heat to 80-85°C, stirring and mixing evenly;

[0074] Step 2: Mix the ingredients of phase B and heat to 80-85°C, stirring and mixing evenly;

[0075] Step 3: Under vacuum, start homogenization of phase A, slowly add phase B into phase A, homogenize at 3000rpm for 5-10min, and keep warm and stir for 10-20min;

[0076] Step 4: Lower the temperature of the ingredients in step 3 to 40-45°C, add the C phase components, stir evenly, and cool to room temperature to obtain the formula preparation example.

[0077] Test Example 1: Instant emulsification effect

[0078] The instant state of each preparation example obtained according to the preparation method in Example 1 is shown in Table 2. The surface appearance of the material body of the instant emulsification effect of Formula Comparative Example 1, Formula Example 3 and Formula Comparative Example 5 is shown in the attached figure. Figure 1 shown.

[0079] Table 2 Formulation preparation example status table

[0080]

[0081] The following table shows the state of the preparation example according to the formula in Table 2: Figure 1 The surface appearance of the material body of the typical formula preparation example shows that the formula examples 1 to 4 can obtain a uniform material body, without precipitation, no floating oil, and the obtained color is within the normal range; while the formula comparative example 1 uses the hydrolyzed soy protein with the same name but non-amphiphilic polypeptide component, has no emulsification effect, and the surface is floating oil; the formula comparative example 2 uses the emulsifier PEG-100 stearate / glycerol stearate, and emulsifies to obtain a uniform milky white material body; the formula examples 1 to 4 and the formula comparative examples 3 to 4 all use the hydrolyzed soy protein of the present invention to obtain a uniform material body; the oil phase thickener of the formula comparative example 5 does not use the oil phase thickener of the present invention, and after emulsification, it precipitates in the solid. Therefore, only the hydrolyzed soy protein with an amphiphilic polypeptide component can obtain a stable material body state, and not all oil phase thickeners are suitable for the composition of the present invention. Only the oil phase thickener within the scope of the present invention can achieve a stable effect.

[0082] Test Example 2 Conductivity Measurement Example

[0083] Each formulation preparation example in Example 1 was placed in a 25°C oven and kept at a constant temperature for 24 hours to ensure that the measured temperature of the formulation preparation example was 25±0.5°C. The conductivity meter was calibrated before the test, and then the test was performed according to the conductivity meter test method. The conductivity test results are shown in Table 3.

[0084] Table 3 Conductivity test results

[0085]

[0086] From the test results in Table 3, it can be seen that the hydrolyzed soy protein emulsified in the present invention is used in formula examples 1 to 4, which has a higher conductivity; the hydrolyzed soy protein used in formula comparative example 1 is not amphiphilic, and the conductivity of the obtained sample is low; formula comparative example 2 uses emulsifier PEG-100 stearate / glycerol stearate for emulsification, and the conductivity of the obtained sample is also very low; formula comparative examples 4 to 5 have a higher conductivity; formula comparative example 3 has a relatively low conductivity because the amount of hydrolyzed soy protein used is too low. It can be seen that amphiphilic hydrolyzed soy protein can make the product obtain high conductivity, but the amount required to be added needs to be within a certain range.

[0087] Test Example 3 High and Low Temperature Stability

[0088] High temperature stability test method: Place each formulation preparation example in Example 1 in a 50°C constant temperature forced air drying oven for 1 month, and observe the appearance and texture of the material after returning to room temperature.

[0089] Low temperature stability test method: Place each formulation preparation example in Example 1 in a refrigerator at -18°C for 1 month, and observe the appearance and texture of the material after returning to room temperature.

[0090] The results of the high temperature stability and low temperature stability tests are shown in Table 4. The surface appearance of the material bodies of Formula Comparative Example 1, Formula Example 3 and Formula Comparative Example 5 after being placed at 50°C for one month is shown in the attached figure. Figure 2 As shown, the surface appearance of the material body of Formula Comparative Example 1, Formula Example 3 and Formula Comparative Example 5 after being placed at -18°C for 1 month is shown in the attached figure. Figure 4 shown.

[0091] Table 4 Stability test results

[0092] sample -18℃ 50℃ Formulation Example 1 normal normal Formulation Example 2 normal normal Formulation Example 3 normal normal Formulation Example 4 normal normal Comparative Example 1 Oil Oil Comparative Example 2 normal normal Comparative Example 4 Demulsification normal Formula Comparative Example 3 normal Oil Formula Comparative Example 5 Demulsification normal

[0093] From the stability test results in Table 4 and the attached Figure 2 and attached Figure 3It can be seen from the surface appearance diagram of the material body of the typical formula preparation example that the stability of formula examples 1 to 4 did not change significantly under high and low temperature test conditions. Formula Comparative Example 1 uses hydrolyzed soy protein without amphiphilicity, and the oil output is unstable at high and low temperatures; although there is no problem with the stability of Formula Comparative Example 2, the conductivity is low in the conductivity test of Test Example 2; Formula Comparative Example 3 has unstable oil output at high temperature due to the low amount of hydrolyzed soy protein used and the high ratio of emollient to hydrolyzed soy protein; Formula Comparative Example 4 has unstable demulsification due to the low ratio of emollient to hydrolyzed soy protein. When the ratio of emollient to hydrolyzed soy protein is low and the content of hydrolyzed soy protein is high, a large amount of hydrolyzed soy protein is free in water, the temperature becomes lower (-18°C), and the hydrophilicity is reduced and precipitated; as the ratio of emollient to hydrolyzed soy protein increases, the hydrolyzed soy protein enters the emollient water interface, the hydrolyzed soy protein free in water becomes less, the temperature becomes lower (-18°C), and the hydrolyzed soy protein does not precipitate. Therefore, the ratio of the emollient to the hydrolyzed soy protein needs to be within the scope of the present invention.

[0094] Test Example 4 Sample Polarizing Microscope Test

[0095] The microscope model used in the test was Nikol Eclipse E200 equipped with a polarizing plate. After the sample of the recipe example and the sample of the recipe comparison prepared in Example 1 were placed at room temperature for 24 hours, a small amount of the sample of the recipe example and the sample of the recipe comparison were taken on a glass slide, and then covered on the sample with a cover glass, and gently pressed until it was translucent, and the magnification was adjusted to 400 times, and the liquid crystal texture was observed under the polarizing microscope, and the image in the eyepiece was photographed with a camera, as shown in the attached figure. Figure 4 shown.

[0096] From the results, it can be seen that the obvious Maltese cross (uniform particle size structure) is seen in Formula Example 1, proving the existence of a liquid crystal structure. This is mainly because when the hydrolyzed soy protein is adsorbed on the water-oil interface, the solid oil phase thickener is interspersed between the hydrolyzed soy protein molecules, making its critical stacking parameter close to 1, and the product with a liquid crystal structure generally has better moisturizing effect and stability. However, the Maltese cross is not seen in the polarizing microscope picture of Formula Comparative Example 2, indicating that no liquid crystal is formed.

[0097] Test Example 5: Active substance electroosmosis test example

[0098] In order to further test whether the active ingredients in a high conductivity system can synergistically enhance the transdermal absorption effect under the action of electric current, thereby exerting better efficacy, the following is a transdermal study of acetyl hexapeptide-8 under the action of a beauty instrument as an example for illustration.

[0099] The electroosmosis test method of acetyl hexapeptide-8 is as follows:

[0100] (1) Preparation of ex vivo suckling pig skin

[0101] The pig back skin stored at -20°C was thawed at 4°C and rinsed repeatedly with PBS after thawing.

[0102] (2) Determination of transdermal absorption capacity

[0103] 1) Sample loading

[0104] Control group: Acetyl Hexapeptide-8 + Beauty instrument turned off: Add the sample to the surface of the pig skin, spread it evenly from the center of the skin to the edge, and use the beauty instrument in the off mode for 15 minutes

[0105] Experimental group: Acetyl Hexapeptide-8 beauty instrument: Add the sample to the surface of pig skin, apply it evenly from the center of the skin to the edge in a radial direction, turn on the beauty instrument, select the third gear, and use it continuously for 15 minutes.

[0106] Each group was repeated 3 times in parallel.

[0107] 2) Fix the pigskin in the Franz-cell diffusion cell, with the stratum corneum of the pigskin facing the donor chamber and the dermis facing the receiving chamber;

[0108] 3) Add 7 mL of receiving solution into the receiving chamber. After the pig skin is tightened and fixed, add 1 mL of receiving solution (PBS) into the receiving chamber through a sampler, exhaust the air, and make the dermis layer of the skin in close contact with the receiving solution.

[0109] 4) Infiltration: Turn on the electromagnetic stirrer and stir at a speed of 300 rpm, maintain a constant temperature water bath of (32±1)°C, and ensure that there are no bubbles in the water bath interlayer.

[0110] 5) The beauty instrument was used for 15 minutes. After 4 hours, skin samples were collected, PBS was aspirated to clean the skin surface 5 times, the residual liquid on the surface was wiped dry with cotton, the skin was circularly cut with a blade, and the pig skin was collected and frozen for subsequent analysis.

[0111] (3) HPLC test of the permeability of acetyl hexapeptide-8

[0112] HPLC-MS was used to detect the amount of acetyl hexapeptide-8 in pig skin tissue. The pig skin needed to be frozen and ground before homogenization. All tissue samples were weighed in a 5ml centrifuge tube, and then 2ml of pre-cooled distilled water was added and homogenized at 4℃70Hz for 360s. After that, ultrasonic oscillation was used for extraction in a 4℃ water bath for 30min, and then cold soaking was used for extraction in a 4℃ refrigerator for 1h. After that, high-speed centrifugation was performed at 4℃, 13000r / min for 15min, and the supernatant was taken and filtered through a 0.22μm filter membrane in a brown injection bottle for determination.

[0113] See the attached for the penetration results of acetyl hexapeptide-8 under the action of beauty instrument. Figure 5 Compared with the control group, under the action of the beauty instrument, the permeability of acetyl hexapeptide-8 increased by 288.53%. Therefore, the active ingredients of the present invention can synergistically enhance the transdermal absorption effect under the action of electric current in a high conductivity system, thereby exerting better efficacy.

[0114] Test Example 6: Thermal Imaging Test of Radio Frequency Beauty Device

[0115] The skin temperature changes of Formula Example 1 and Formula Comparative Example 2 in Example 1 were tested with a thermal imager (Fotric 618C) before and after use with the Ya-Man ACE6 radio frequency beauty instrument.

[0116] The specific test steps are as follows:

[0117] (1) Before using the product (D0): Upon arrival, the subjects cleaned the test area with the cleansing product provided by the laboratory, gently dried it with a dandruff-free dry facial tissue, and sat quietly in the laboratory at a temperature of 21±1°C and a relative humidity of 50±10% for 20 minutes; the laboratory tester distributed the sample, applied it evenly on the test area of ​​the arm, and then used a thermal imager (Fotric618C) to collect and measure the skin temperature image of the test area of ​​the arm.

[0118] (2) Immediately after using the product (30 seconds): After using the product, the subject moves the Ya-Man ACE6 radio frequency beauty device on the skin of the test area at a constant speed for 30 seconds. The laboratory tester uses a thermal imager to collect and measure the skin temperature image of the test area on the arm.

[0119] (3) Use the software provided by the thermal imager to analyze the skin temperature image of the recorded area to obtain the maximum temperature Tm of the skin in the test area.

[0120] The thermal imaging test results are as attached. Figure 6 As shown, the highest temperature Tm of the skin in the test area after the formula comparative example 2 is used with the radio frequency beauty instrument is 35.2°C, and the highest temperature Tm of the skin in the test area after the formula example 1 sample is used with the radio frequency beauty instrument is 37.7°C. Therefore, when the formula example 1 and the formula comparative example 2 are used in combination with the radio frequency beauty instrument, the skin of the formula example 1 can reach a higher temperature within the same use time, which is more conducive to the effect of the radio frequency beauty instrument.

[0121] In summary, in the high conductivity composition of the present invention, it is concluded through the instant emulsification effect that only the hydrolyzed soy protein with an amphiphilic polypeptide component can obtain a stable material state, and not all oil phase thickeners are suitable for the composition of the present invention, and only the oil phase thickeners within the scope of the present invention can achieve a stable effect; through the determination of conductivity, the amphiphilic hydrolyzed soy protein can make the product obtain high conductivity, but the amount to be added needs to be within a certain range; at the same time, the high temperature stability and low temperature stability tests show that the ratio of the emollient to the hydrolyzed soy protein needs to be within the range of the present invention, if it is not within the ratio range of the present invention, demulsification and other instability phenomena will occur.

[0122] The above is only a preferred embodiment of the invention, and is not intended to limit the invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the invention shall be included in the protection scope of the invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the invention, which all belong to the protection scope of the invention. Therefore, the protection scope of the patent of the invention shall be based on the attached claims.

Claims

1. A high conductivity composition, characterized in that: The high-conductivity composition comprises 0.5-1.5 mass % of hydrolyzed soybean protein, 10-40 mass % of emollient, 0.5-7 mass % of oil phase thickener and the balance of aqueous components, based on 100 mass % of the high-conductivity composition.

2. A high conductivity composition according to claim 1, characterized in that: The high-conductivity composition comprises 0.7% to 1.5% by mass of hydrolyzed soybean protein, 10% to 30% by mass of an emollient, 0.5% to 5% by mass of an oil phase thickener, and the balance of an aqueous component, relative to 100% by mass of the high-conductivity composition.

3. A high conductivity composition according to claim 1, characterized in that: The mass ratio of the hydrolyzed soy protein to the emollient is 1:(15-25), preferably 1:(15-20).

4. A high conductivity composition according to claim 1, characterized in that: The molecular weight of the hydrolyzed soybean is 10,000 to 30,000 Daltons.

5. A high conductivity composition according to claim 1, characterized in that: The oil phase thickener is at least one of pentaerythritol tetrastearate, dextrin palmitate, synthetic wax, synthetic spermaceti, cetyl palmitate, cetyl alcohol, stearyl alcohol, cetearyl alcohol, and stearic acid, preferably at least one of cetearyl alcohol and cetyl palmitate.

6. A high conductivity composition according to claim 1, characterized in that: The emollient is at least one of jojoba seed oil, meadowfoam seed oil, avocado butter, inca inchi seed oil, oat kernel oil, safflower seed oil, squalane, hydrogenated polyisobutene, hydrogenated polydecene, caprylic / capric triglyceride, dimethicone, coconut oil caprylate / caprate, pentaerythritol tetra(ethylhexanoate), and propylene carbonate, preferably at least one of hydrogenated polyisobutene, dimethicone, and caprylic / capric triglyceride.

7. A method for preparing the high conductivity composition according to any one of claims 1 to 6, characterized in that: The emollient and the oil phase thickener are heated to 80-85° C. to obtain the oil phase component; the hydrolyzed soy protein and the aqueous component are evenly mixed and heated to 80-85° C. to obtain the water phase component; the oil phase component is added to the water phase component and then homogenized and emulsified to obtain a high conductivity composition.

8. A cosmetic composition of the high conductivity composition according to any one of claims 1 to 6, characterized in that: The present invention is composed of 10 to 40% by mass of an emollient, 0.5 to 1.5% by mass of a hydrolyzed soy protein, 0.5 to 7% by mass of an oil phase thickener, 1 to 10% by mass of a polyol, 0.1 to 1% by mass of an aqueous thickener, 1 to 5% by mass of an active ingredient, 0.5 to 1.5% by mass of a preservative and the balance of water, relative to 100% by mass of the cosmetic.

9. The cosmetic composition of high conductivity composition according to claim 8, characterized in that: The cosmetic is any one of lotion, essence or emulsion.

10. A combination of the high conductivity composition according to any one of claims 1 to 6 and a beauty instrument, characterized in that: The beauty instrument is any one of a radio frequency beauty instrument or a micro current beauty instrument.

Citation Information

Patent Citations

  • Liquid emulsion cosmetic

    CN1917850B